Assessmentof Hair Growth Treatment with the Consciousness Energy Healing Treated Williams Medium E Using Mouse Vibrissae Hair Follicle Organ Culture - Kumar Trivedi, Mahendra; Jana, Snehasis (Journal of Dermatologic Research And Therapy, 2019)
Hair is playing an interesting part in human for social and sexual communication. Loss of hair follicle leads to various skin disorders. For this consequence, the present study has investigated the potential of the Biofield Energy Healing (The Trivedi Effect®) Treated test item (William’s Medium E) on the vibrissae hair follicle organ culture cells for the assessment of hair cell growth and development in vitro. The test item was divided into two parts. One part was defined as the untreated test item, where no Biofield Energy Treatment provided, while the other part was defined as the Biofield Energy Treated test item, which received the Biofield Energy Healing Treatment by renowned Biofield Energy Healer, Mahendra Kumar Trivedi. The study parameters like bulb thickness and formation of telogen were assessed using cell-based assay with the help of UTHSCSA Image tool version 3. The experimental results showed that the untreated test item group showed 20.9% and 28.2% increased bulb thickness on day 5 and 7, respectively compared to the day 1, while did not produce telogen follicles upto day 7. Besides, the percentage of telogen follicle was found as 43%, 57%, and 71% on day 3, 5, and 7, respectively of the Biofield Energy Treated test item group compared to the day 1. The overall results demonstrated that the Biofield Energy Treatment has the potential for hair growth promotion as evident via increased the formation of telogen. Therefore, the Biofield Energy Healing (The Trivedi Effect®) Treatment might be useful as a hair growth promoter for various treatment of skin injuries and skin-related disorders like necrotizing fasciitis, actinic keratosis, sebaceous cysts, diaper rash, decubitus ulcer etc.
Keywords: Hair Growth; Vibrissae Hair Follicle; Hair Follicle Organ Culture; Bulb Thickness; Williams Medium E; Ex Vivo Hair Growth